2018
DOI: 10.30880/jts.2018.10.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Kajian Pandangan Pihak Pembuat Dasar Terhadap Konsep Kolej Kediaman Lestari Di Universiti Awam Malaysia

Abstract: Kolej kediaman dibangunkan sebagai sebahagian komponen yang melengkapkan keseluruhan universiti. Kolej kediaman bertindak sebagai pusat perumuahan pelajar. Menurut Darus (2006), kolej kediaman merupakan sebahagian daripada komponen utama di dalam institut pengajian tinggi yang menyediakan kemudahan penginapan dan makanan serta mengadakan aktiviti-aktiviti pembangunan pelajar kepada mahasiswa di universiti. Menurut Alwee et al. (2008), kolej kediaman merupakan kemudahan yang disediakan oleh universiti bagi peng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Hearing-impaired students were not provided adequate sign language interpreters, visually impaired students struggled with using computers, and most students with disabilities expressed difficulties with on-campus infrastructure and transportation systems. Almost a decade after, several studies (Buyung and Shafii, 2015;Yusof et al, 2020, among others) reported similar results to Toran et al (2009), which implies 'slow' progress in building inclusive facilities for people with disabilities in HEIs. For example, Buyung and Shafii (2015) discussed students with disabilities' accommodation problems in HEIs and concluded that the provided infrastructures were not accessible, did not meet the students' needs and were of low quality.…”
Section: Introductionmentioning
confidence: 65%
See 2 more Smart Citations
“…Hearing-impaired students were not provided adequate sign language interpreters, visually impaired students struggled with using computers, and most students with disabilities expressed difficulties with on-campus infrastructure and transportation systems. Almost a decade after, several studies (Buyung and Shafii, 2015;Yusof et al, 2020, among others) reported similar results to Toran et al (2009), which implies 'slow' progress in building inclusive facilities for people with disabilities in HEIs. For example, Buyung and Shafii (2015) discussed students with disabilities' accommodation problems in HEIs and concluded that the provided infrastructures were not accessible, did not meet the students' needs and were of low quality.…”
Section: Introductionmentioning
confidence: 65%
“…Almost a decade after, several studies (Buyung and Shafii, 2015;Yusof et al, 2020, among others) reported similar results to Toran et al (2009), which implies 'slow' progress in building inclusive facilities for people with disabilities in HEIs. For example, Buyung and Shafii (2015) discussed students with disabilities' accommodation problems in HEIs and concluded that the provided infrastructures were not accessible, did not meet the students' needs and were of low quality.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…Efforts to use technology are gaining traction on a global scale, especially in higher institutions and universities. It is well documented in the news that the presence of the Fourth Industrial Revolution (4IR) has some impact on the education sector, including higher education [18]. The 4IR means a comprehensive and rapid change in the industry that is closely related to the rapid development of technology [6].…”
Section: Introductionmentioning
confidence: 99%